Protocol update to: High-throughput scNMT protocol for multiomics profiling of single cells from mouse brain and pancreatic organoids - Santiago Cerrizuela; Oguzhan Kaya; Lukas P.M. Kremer; Andrea Sarvari; Tobias Ellinger; Jannes Straub; Jan Brunken; Andrés Sanz-Morejón; Aylin Korkmaz; Ana Martín-Villalba (STAR Protocols, 2025)
Summary: Single-cell nucleosome, methylome, and transcriptome (scNMT) sequencing is a recently developed method that allows multiomics profiling of single cells. In this scNMT protocol, we describe profiling of cells from mouse brain and pancreatic organoids, using liquid handling platforms to increase throughput from 96-well to 384-well plate format. Our approach miniaturizes reaction volumes and incorporates the latest Smart-seq3 protocol to obtain higher numbers of detected genes and genomic DNA (gDNA) CpGs per cell. We outline normalization steps to optimally distribute per-cell sequencing depth.For complete details on the use and execution of this protocol, please refer to Kremer et al. and other works.1,2,3,4,5,6,7This protocol is an update to Cerrizuela et al.7 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.